Governance Through Regime Complexity: What Role for the EU in the African Security Regime Complex? - Brosig, Malte (2023)
The international response to armed conflict in Africa often takes the form of a regime complex characterized by institutional proliferation, overlap, unclear hierarchies, and multiple interconnections. At the same time, the course of conflict is hardly predictable. In such an environment, how can component units (institutional fora) of a regime complex effectively govern through complexity? We explore this question by focusing on the EU as an important actor within regime complexes. Building on the regime complexity literature and complexity theory, we identify four conditions. We argue that actors who operate as resource hubs, create complementarity, support system self-organization, and practice adaptive forms of peacebuilding are best placed to manage regime complexity. Empirically we probe these assumptions in the context of the Sahelian security regime complex and the role the EU is playing in it.